2021
DOI: 10.1038/s41591-021-01593-2
|View full text |Cite
|
Sign up to set email alerts
|

Real-time alerting system for COVID-19 and other stress events using wearable data

Abstract: Early detection of infectious diseases is crucial for reducing transmission and facilitating early intervention. In this study, we built a real-time smartwatch-based alerting system that detects aberrant physiological and activity signals (heart rates and steps) associated with the onset of early infection and implemented this system in a prospective study. In a cohort of 3,318 participants, of whom 84 were infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), this system generated alerts… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 20 publications
2
77
0
2
Order By: Relevance
“…We first investigated the baseline scenario in which detection algorithms that currently exist are made publicly available for device users to download and use (Figure 2) 10 . Upon notification of potential presymptomatic or asymptomatic infection, users are prompted to seek a confirmatory lab-based test, self-isolate while awaiting the result (nominally, for 2 days), and quarantine until recovery if positive.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We first investigated the baseline scenario in which detection algorithms that currently exist are made publicly available for device users to download and use (Figure 2) 10 . Upon notification of potential presymptomatic or asymptomatic infection, users are prompted to seek a confirmatory lab-based test, self-isolate while awaiting the result (nominally, for 2 days), and quarantine until recovery if positive.…”
Section: Resultsmentioning
confidence: 99%
“…The social and economic harm caused by solely promoting uptake or adherence without improvements to detection specificity would likely undermine public confidence in and compliance with a wearable-based pandemic mitigation strategy 22 . Alavi et al found that many false positives were due to the detection algorithm identifying lifestyle- driven changes in resting heart rate (e.g., after intense exercise or alcohol consumption); accounting for these factors using more advanced algorithms may be one way to target improved detection specificity 10 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations